1993
DOI: 10.1021/bi00210a015
|View full text |Cite
|
Sign up to set email alerts
|

Controlled formation of model homo- and heterodimer coiled coil polypeptides

Abstract: Sequence-simplified coiled coil polypeptides were synthesized and their folding properties characterized in order to define the role of charged border residues at the coiled coil interface for the controlled formation of homodimer and heterodimer structures. Three peptides were designed to form parallel coiled coils with valine and leucine occupying the hydrophobic interface positions a and d, respectively, of the heptad repeat abcdefg. The polypeptide designated E/K42, with the heptad repeat sequence VSSLESK,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
155
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(167 citation statements)
references
References 33 publications
(37 reference statements)
10
155
2
Order By: Relevance
“…We have designed a heterodimeric coiledcoil ( Figure 1 and Table 1), based on principles revealed by more than 15 years of investigation (13,16,17,22). The primary stabilizing interactions are the hydrophobic interactions in the core (34,37), electrostatic attractions across the interface (5,7,9,16), and helical propensity (16,(38)(39)(40)(41).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have designed a heterodimeric coiledcoil ( Figure 1 and Table 1), based on principles revealed by more than 15 years of investigation (13,16,17,22). The primary stabilizing interactions are the hydrophobic interactions in the core (34,37), electrostatic attractions across the interface (5,7,9,16), and helical propensity (16,(38)(39)(40)(41).…”
Section: Resultsmentioning
confidence: 99%
“…This demonstrated that the contribution of Leu-Leu hydrophobic interactions to the stability of the coiled-coil structure were less important at the ends of the coiled-coil, and that the ends of the coiled-coil were more flexible. More recently, Holtzer et al (65) clearly demonstrated by 13 C R chemical shifts that such an end-fraying also occurred in a GCN4-like leucine zipper. All these studies suggest that the different heptads which make up a dimeric coiled-coil structure contribute differently to its stability; the heptads located at the ends of the coiled-coil are able to fray whereas the ones composing the core of the coiled-coil are more stable due to the tighter packing of the hydrophobic residues.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The failure of putative repulsive interactions to prevent heterodimer formation presumably reflects differences in the sensitivities of the homodimerization and heterodimerization assays in vivo. It should be noted that, because our genetic test currently requires that the mutants we tested be able to form fusion proteins with strong enough dimerization to be detected as functional repressors, our data set includes no examples of pairs where the formation of heterodimers leads to a net increase in the number of attractive ion pairs, as would be observed with Fos-Jun heterodimers and in the designed heterodimers with acidic and basic monomers (O'Shea et al, 1992(O'Shea et al, , 1993Graddis et al, 1993;Zhou et al, 1994a). In these cases, the pH dependence of homodimer and heterodimer formation suggests that charge-charge interactions play a role in determining specificity.…”
Section: Each Row Shows Results For One Cl' Fusion Protein Expressementioning
confidence: 99%
“…Hydrophobic amino acids are often present at the a and d "buried" positions every 3.6 residues, and polar/charged residues are at the adjacent flanking e and g "surface" positions (11)(12)(13)(14)(15). At this interval, a hydrophobic dimerization interface (core) is created, surrounded by interhelical electrostatic interactions that may dictate protein interaction specificity.…”
mentioning
confidence: 99%